New Noctuidae (s.l.) species from the Korean fauna with description of a new species of Bryophila Treitschke, 1825 (Lepidoptera: Erebidae and Noctuidae) - An, Jeong-Seop; Choi, Sei-Woong; Ronkay, László (Zootaxa, 2013)
Eight Erebidae and Noctuidae species are reported for the first time from Korea. The taxonomic positions of another two formerly misidentified species, Abrostola korbi and Diachrysia witti, are discussed. The Korean species of the Bryoleuca granitalis species-group are characterised and a new species of the group, Bryoleuca volodia sp. n. from Vietnam, is described and illustrated.